Categorisation of actions by leaders in South Africa in terms of the Head, Heart and Hands model . - Burger, Ronél (My University, 2014)
ABSTRACT This research investigates how leaders categorise their actions in terms of the Head, Heart and Hands model (Goleman, Boyatzis & McKee, 2004) and which one of the three sections is perceived to be most important and why, along with a view on whether the model is an appropriate framework to recommend to future leaders for categorisation of their actions. A qualitative approach was deemed suitable as it is particularly concerned with understanding multiple perspectives of different individuals (Leedy & Ormrod, 2005; Williams, 2007). It utilised semi-structured interviews with a number of respondents, all effective South African leaders, who have demonstrated successful leadership and have at least five years executive management experience. The intention was to develop an understanding of the respondents‟ perspectives as to which of their daily actions they consider to have contributed to their efficacy, and how these activities are categorised into the Head, Heart and Hands model (Goleman, et al., 2004). Each of the respondents spontaneously categorised their top three activities under each of the three elements of the head, the heart or the hands, despite being informed that they could place more than one in the same category. It was difficult for the majority of respondents to put their top three activities in order of preference, however a tally after the first and second choice was nominated, showed all respondents choosing the heart as either a first or second choice. The head was chosen as a first or second choice by 10 of the respondents and the hands by only two. Although it seems that the Head, Heart and Hands model (Goleman et al., 2004) could be considered as a good model to categorise the actions of an effective leader, there is no clear indication of which element is considered to be most important or indispensable to exceptional leaders as the scoring was very similar for the heart and the head elements. In future a larger sample would ensure better generalizability and aid in the building of a model to adopt when embarking on the journey towards effective leadership.
MBA 2013
Keywords: Leadership